SANAD-BASED DAKWAH METHOD: A STUDY OF THE TEACHING TRADITION AND EXAMPLE OF K.H. MUHAMMAD ARWANI AMIN SA'ID KUDUS - Imam Fatkhullah; Yuzril Mahendra; Muhammad Firdaus (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This study is motivated by the decline of moral and spiritual authority in  modern Islamic da’wah, which tends to be pragmatic and rhetorical. The research  aims to analyze the sanad-based da’wah method practiced by K.H. Muhammad  Arwani Amin Sa’id at Yanbu‘ul Qur’an Islamic Boarding School in Kudus as a  model emphasizing the continuity between knowledge (‘ilm), ethics (adab), and  practice (‘amal). Using a qualitative approach through library research, this study  examines Arwani’s works, biography, and teaching tradition. The findings reveal  that sanad in Arwani’s da’wah functions as a system of value transmission  integrating intellectual, moral, and spiritual dimensions through talaqqi (direct  learning), mushafahah (face-to-face transmission), and exemplary conduct (uswah  hasanah). This approach unites sanad al-‘ilm, sanad al-adab, and sanad al-amal,  resulting in an authentic and transformative da’wah bil hal (preaching through  action). This study concludes that sanad da'wah is a relevant paradigm for  contemporary Islamic da'wah which is rooted in tradition but oriented towards  character formation. Its implication suggests that this model can be  recontextualized in education and digital da’wah to strengthen scholarly authority,  ethical integrity, and moderate Islamic leadership in the modern era.